2018
DOI: 10.1177/1354816618801504
|View full text |Cite
|
Sign up to set email alerts
|

International tourism demand, number of airline seats and trade triangle: Evidence from New Zealand partners

Abstract: This article examines the three-way relationship between international tourism demand, airline economy seats and international trade for New Zealand together with its key trading/tourism partners. We have found that airline economy seats are the important factor for determining tourism demand among New Zealand's tourism partners except for richer economies, like the United States and Japan. Trade volume does not have strong causality relationship to tourism demand in particular for trading partners, like Japan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Data were collected from the International Civil Aviation Organization (ICAO). These variables reflect a reduction in air traffic for origins and destinations, a factor that can shape bilateral tourism demand ( Ozer Balli, Balli, and Tsui 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected from the International Civil Aviation Organization (ICAO). These variables reflect a reduction in air traffic for origins and destinations, a factor that can shape bilateral tourism demand ( Ozer Balli, Balli, and Tsui 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Air transport and tourism are generally mutually dependent [3,18]. On the one hand, air transport facilitates tourism, since aviation services provide accessibility over large spatial networks; on the other hand, much of the demand for air transport services is derived from tourism activities (e.g., [19][20][21][22][23]). However, such mutual dependence ensures a Fig.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the air transport and tourism literature, it is generally acknowledged that air accessibility and seat capacity have promoted tourism growth (e.g., [23,24]). In particular, the development of LCCs has had substantial impacts on tourism demand regarding inbound air travelers and the promotion of tourist destinations, since LCCs provide more affordable air travel (e.g., [24][25][26]).…”
Section: Determinants Of Inbound International Tourismmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards the literature, papers related to the study presented here generally concentrated on causality between demand for air transport and demand for tourism or economic growth (Balli et al, 2019;Balsalobre-Lorente et al, 2020;Fernandes et al, 2019a;Koo et al, 2017;Njoya & Nikitas, 2020;Sonnenburg & Braun, 2017;Zhang & Graham, 2020). Using an input-output analysis of inter-industrial relations in Germany, Kowalewski (2013) found that, of all the industries studied, air transport had the greatest multiplier effect on employment.…”
Section: Introductionmentioning
confidence: 99%